2022
DOI: 10.1021/acssensors.2c00794
|View full text |Cite
|
Sign up to set email alerts
|

Passive and Flexible Wireless Electronics Fabricated on Parylene/PDMS Substrate for Stimulation of Human Stem Cell-Derived Cardiomyocytes

Abstract: In this paper, we report the development of a wireless, passive, biocompatible, and flexible system for stimulation of human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CMS). Fabricated on a transparent parylene/PDMS substrate, the proposed stimulator enables real-time excitation and characterization of hiPSC-CMs cultured on-board. The device comprises a rectenna operating at 2.35 GHz which receives radio frequency (RF) energy from an external transmitter and converts it into DC voltage to deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Before testing the proposed wireless implant, a preliminary study was conducted to determine and compare the voltage and current for triggering limb movement using the proposed e-dura substitute method versus the conventional direct epidural stimulation method, in the absence of a dura substitute. In this experiment, a wireless stimulator that we designed and fabricated on a Rogers 6010 substrate (referred to as 6010 stimulator) was used [ 38 ]. The stimulator has a similar circuit structure as the proposed wireless implant, and it is equipped with energy storage capacitors with an identical value (30 μ F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before testing the proposed wireless implant, a preliminary study was conducted to determine and compare the voltage and current for triggering limb movement using the proposed e-dura substitute method versus the conventional direct epidural stimulation method, in the absence of a dura substitute. In this experiment, a wireless stimulator that we designed and fabricated on a Rogers 6010 substrate (referred to as 6010 stimulator) was used [ 38 ]. The stimulator has a similar circuit structure as the proposed wireless implant, and it is equipped with energy storage capacitors with an identical value (30 μ F).…”
Section: Resultsmentioning
confidence: 99%
“…While other methods exist for enhancing the adhesion of gold to PDMS, we rely on parylene because it offers other desirable properties, such as low permeability to moisture (Dimer C). In our previous work [ 38 ], we found that the combination of parylene/PDMS maintains excellent transparency with a parylene layer thickness of up to 20 μ m. Clear observation of cultured human-derived cardiomyocytes was possible using an inverted fluorescence microscope (Axio Observer Z1, Zeiss). A parylene passivation layer (2 μ m) is added to protect and electrically isolate the electronics.…”
Section: Methodsmentioning
confidence: 99%
“…Beating behavior of the cardiac tissues were analyzed as described in our recent publications. Briefly, cardiac tissue samples were placed on the stage of a Zeiss microscope, and phase contrast images of the cardiac tissues were obtained at days 3, 7, and 14 of culture using a 10× objective. Time-lapse images were acquired (10×) for 20 s on day 14 to examine spontaneous or stimulated contraction of the cardiac tissues.…”
Section: Methodsmentioning
confidence: 99%